Bataville : identité confuse d’un héritage d’urbanisme industriel autoritaire - Sophie Suma (Projets de Paysage)
The image reflected of Bataville in its heyday is an attractive one, however, today the identity of this site in the Moselle region is less easily defined. Based on the history and the background to the creation of this factory-town project, and by examining the different formal and ideological representations that emerge from the plan, as well as those relating to heritage, is it possible to grasp the autarchic dimension of the complex, which seems to have been induced by the architectural and semi-urbanistic layout imagined by its designers ? To what extent was this isolation a strategy devised by the company Bata S.A. to control bodies and spaces ? What were the consequences of this confinement following the company’s departure ?